A novel concentrated growth factor (CGF) and bio-oss based strategy for second molar protection after impacted mandibular third molar extraction: a randomized controlled clinical study - Shoufu Sun; Xiaodong Xu; Zhongxiao Zhang; Ying Zhang; Wenjia Wei; Ke Guo; Yunan N. Jiang (BMC, 2023)
Abstract Background The extraction of impacted mandibular third molars might cause large bone defects in the distal area of second molars. A new strategy was innovatively employed here combining autologous bone, Bio-Oss, concentrated growth factors (CGF) gel and CGF membrane for bone repair, and the present study aimed at exploring safety as well as short- and long-term efficacy of this new protocol clinically. Materials and methods A total of 66 participants were enrolled in this randomized single-blind clinical trial, and randomly allocated to control group (only blood clots), test A group (autogenous bone, Bio-Oss with barrier membrane) and test B group (autogenous bone, Bio-Oss, CGF gel with CGF membrane). The postoperative outcomes including PoSSe scale, periodontal probing depth (PD), degree of gingival recession and computed tomography measurements were assessed at 3rd, 6th, 12th month. A p-value < 0.05 was considered statistically significant. Results In PoSSe scale, no significant difference was observed except a significant alleviation of early-stage pain perception in test B group (p < 0.05). Also, test B group exhibited better effect on periodontal healing and gingival recession reduction after 6 months (p < 0.05). Both two test groups showed more new bone formation than the control group (p < 0.05). It is noteworthy that the bone repair of test B group was significantly better than that of test A at 3rd and 6th month (p < 0.05), yet no difference was observed at 12th month (p > 0.05). Conclusion Both two test groups could achieve stable long-term efficacy on bone defect repair. The use of CGF gel and CGF membrane could accelerate early-stage bone repair, alleviate short-term pain after surgery, reduce long-term probing depth and relieve economic cost for patients. This new bone repair protocol is worthy of promoting by clinicians. Trial registration This study was registered with the identification number ChiCTR2300068466 on 20/02/2023 at Chinese Clinical Trial Registry. Also, it was ethically approved from the institutional ethics committee at the Tongren Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, China (No:2023-010-01), and has been conducted in accordance to the guidelines of the declaration of Helsinki. Written informed consent was obtained from all participants in the study.